Effectiveness of employee compensation strategies on improving employee performance in the minerals marketing sector in Zimbabwe: a case of Minerals Marketing Corporation of Zimbabwe (MMCZ) - Gomwe, Nelisha, G. (Midlands State University, 2017)
The study sought to find out the effectiveness of employee compensation strategies on employee performance. A case of Minerals Marketing Corporation of Zimbabwe was used. The main objectives of the research were to determine the impact of a basic pay on employee commitment, to assess the influence of commission based reward on employee productivity in the minerals marketing sector and to measure the effectiveness of fringe benefits on worker absenteeism. The study reviewed that compensating employees using fringe benefits will help in increasing employee motivation and this will lead to reduced employee absenteeism. In addition, it was also argues that a commission based pay influences the productivity of employees. Employees who are motivated by money to produce more are the ones that are largely influenced by commission based pay. Furthermore it was reviewed that a basic pay offered to employees leads to employee commitment. Relevant literature for the research was obtained from textbooks as well as online journals. A sample size of 33 was drawn from Minerals Marketing Corporation of Zimbabwe in Harare and Gweru. Judgmental sampling and convenience sampling techniques were used for both the management and employee and descriptive and exploratory research designs were used in utilizing quantitative and qualitative data which was gathered to address the stated objectives through questionnaires, interviews and observation. The findings also revealed that Minerals Marketing Corporation of Zimbabwe has a few and inadequate compensation packages that are currently being used. It also revealed that fringe benefits will increase motivation of the employees thus reducing worker absenteeism. It was observed through the findings that a commission based pay is very influential in increasing the productivity of employees. Moreover, the findings revealed that a basic salary that is competitive will increase employee commitment. The researcher recommended that management is challenged to continuously provide compensation packages that motivate different employees at different levels at a way that will help them increase productivity and commitment at the corporate. Various types of fringe benefits should be provided by the cooperation to ensure that there are high levels of motivation amongst employees. The researcher suggests that further research should be done on the evaluation of non-financial motivational strategies on sales revenue.